Analysis of Final TaxAtion on Construction Services Companies Listed on the Indonesia Stock Exchange Year 2015-2019 - januri januri (International Journal Reglement & Society (IJRS), 2020)
This study aims to analyze about the imposition of final taxes on construction services companies. This research will discuss before and after the implementation of the Final Income Tax on construction services to find out the comparison of the two and to find out the resulting reform goals whether or not to create a balanced tax system. Data collection techniques in this research is quantitative. The analysis techniques used are descriptive, where the author describes in detail the existing data of each activity related to the Final Income Tax of construction services companies. Through the indicators described in the writing, the author will see the difference before it is applied and after the implementation of the Final Income Tax on construction services in each company. If the application of the Final Income Tax can reduce the burden of taxation on the company then the Final Income Tax on construction services has created a balanced taxation system, and vice versa.